Walking as a Modality for Enhancing Physical Fitness: A Review - Rachel Maya; Irfannuddin; Siti Sarahdeaz Fazzaura Putri (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Walking plays a key role in maintaining overall physical fitness which is essential for good health. Physical fitness consists of two main aspects health-related and skill-related components. It is commonly measured by assessing cardiovascular endurance muscle strength muscle endurance flexibility and body composition. This review conducted a comprehensive literature search using reputable publications such as Elsevier, PubMed, PubMed Central, and other relevant sources. The search focused on peer-reviewed studies that examine the effects of walking on physical fitness. Many studies highlight walking as a simple and accessible form of exercise that offers significant benefits such as improved cardiovascular endurance muscle strength and flexibility. It is recommended to engage in at least 150 minutes of walking each week for optimal benefits. To maximize walking's impact on fitness it is crucial to maintain good posture and proper breathing techniques. In addition to physical benefits walking also promotes mental and social well-being. It is a versatile activity suitable for all ages including adolescents, adults, children, seniors, and individuals with specific health conditions or diseases. By understanding the connection between walking and fitness people can incorporate it into their daily routines to enhance overall health. Future research could focus on specific fitness aspects related to walking to develop personalized guidelines for different populations.